Farmers' Sources and Varieties of Cassava Planting Materials in Coastal Kenya - Kidasi, Patrick Clay; Chao, Dora Kilalo; Obudho, Elias Otieno; Mwang'ombe, Agnes Wakesho (Frontiers in Sustainable Food Systems, 2021)
Abstract Cassava (Manihot esculenta Crantz) grows in diverse agro-ecological zones. In Kenya, cassava is widely cultivated in Western and Coastal regions. However, scarcity of cassava cuttings forces cassava farmers to source and recycle from informal seed sources, where these practices are associated with negative impacts on acreage and productivity of cassava. Focused group discussions (FGD) and survey were conducted using a semi-structured questionnaire targeting 250 farmers. This study purposed to determine the farmers' sources and varieties of cassava planting materials in coastal Kenya. Statistical Package for Social Sciences was used for data analysis. The sources of cassava planting materials recorded were farmers’ (83%), neighbors' (67%), local market's (5%) and Kenya Agricultural and Livestock Research Organization’s (KALRO) seed (11%). Amongst the sources, KALRO was the only formal seed source. Informal seed sources especially farmers’ and neighbors’ were prominent as a result of the piecemeal harvesting technique (98%). Based on quantities of cuttings, a majority (87.2%) of farmers in Taita Taveta County plant <100 cuttings whereas 56% from Kilifi County plant between 100 and 4000 cuttings. Most farmers had <0.2 Ha under cassava with 60% and 72.8% in Kilifi and Taita Taveta counties, respectively. A majority (81.1%) of farmers in Taita Taveta plant local cassava varieties as compared to Kilifi County (57.8%). In terms of preference, Kibandameno (52%) was leading followed by Tajirika (18%). Kibandameno is preferred because of sweet taste (75.6%) while Tajirika of high yielding (52.4%). However, farmers sourcing from the formal source are more likely to be from Kilifi County where cassava is highly valued and within a cassava group for gaining knowledge on cassava production. As for informal seed sources, they are more likely to be sourced by farmers with low knowledge of cassava production and low earnings. Therefore, the availability of cuttings can potentially increase cassava acreage and productivity for food security, however, knowledge in selecting varieties and cuttings for planting was vital in achieving them.